Autophagy in Macrophages: Impacting Inflammation and Bacterial Infection. (9th April 2014) - Vural, Ali; Kehrl, John H.
Abstract : Macrophages are on the front line of host defense. They possess an array of germline-encoded pattern recognition receptors/sensors (PRRs) that recognize pathogen-associated molecular patterns (PAMPs) and which activate downstream effectors/pathways to help mediate innate immune responses and host defense. Innate immune responses include the rapid induction of transcriptional networks that trigger the production of cytokines, chemokines, and cytotoxic molecules; the mobilization of cells including neutrophils and other leukocytes; the engulfment of pathogens by phagocytosis and their delivery to lysosome for degradation; and the induction of autophagy. Autophagy is a catabolic process that normally maintains cellular homeostasis in a lysosome-dependent manner, but it also functions as a cytoprotective response that intersects with a variety of general stress-response pathways. This review focuses on the intimately linked molecular mechanisms that help govern the autophagic pathway and macrophage innate immune responses.